Performance of rabbits on mash mixture feed and pellet feed supplemented with guinea grass - Mohamad Mazalan, Fateen Syifa Nadhirah (2017)
This experiment was conducted in Ladang 2, Universiti Putra Malaysia and 15 male New Zealand White rabbits, age of four weeks old, were used in this experiment. This project include five treatment groups. Treatment 1 (PGg) received 80% pellet feed + 20% Guinea grass, Treatment 2 (P60MGg) received 60% pellet feed and 20% mash mixture feed + 20% Guinea grass, Treatment 3 (P40MGg) received 40% pellet feed and 40% mash mixture feed + 20% Guinea grass, Treatment 4 (P20MGg) recieved 20% pellet feed and 60% mash mixture feed + 20% Guinea grass and Treatment 5 (MGg) recieved 80% mash mixture feed + 20% Guinea grass respectively. The main purpose of this study, to examine the effect of different form of rabbit feed on growth performance of rabbits and it influence on body weight of the rabbits. Specifically, the study aimed to determine the growth performance of rabbits fed with pelleted form feed and mash feed mixtures. In recent times, attention has shifted to rabbits as meat animals. Many of Mediterranean countries already include rabbit meat as a common food (Dalle Zotte and Szendro, 2011). Based on the nutritional view, rabbit meat is kind of ideal meat for all kinds of consumer. However, that scenario does not happen yet in Malaysia because of many factors, such as the demand itself influences the production system. Commercial feeds are also expensive and can be a constraint to potential of rabbits to meet the protein needs. It is also will increase operation cost to the farmers. The cost of rabbit feed can be reduced if other feed substitution such as mash mixture feed which can also serve the adequate nutrient supply to the rabbits being used. All the rabbits were housed individually. Rabbits were distributed randomly to each of the treatment groups equally with three rabbits in each group. All the rabbits were supplied ad libitum green grass (Guinea grass). Concentrate feed were given to each group according to the treatment assigned. Water supply were provided all the time to the rabbits. Amount of feed residue were collected every morning before the feed were given to the rabbits on that the rabbits were supplied ad libitum green grass (Guinea grass). Concentrate feed were given to each group according to the treatment assigned. Water supply were provided all the time to the rabbits. Amount of feed residue were collected every morning before the feed were given to the rabbits on that day, to measure the actual feed intake of the rabbits for previous day. Body weight of the rabbits were measured once in a week, early in the morning before the feed was given to the rabbits, to get the body weight gain for every week.Collected data for every parameter were analyzed using Statistical Analysis System (SAS) 9.4 programme to compute analysis of variance (ANOVA) for a completely randomized design (CRD); Duncan’s Multiple Range Test (DMRT) was done to compare the treatment means for different parameters. The results of growth performance of rabbits fed ad libitum green grass (Guinea grass) along with either pellet, mash or pellet and mash feed were shown did not differ significantly (P>0.05) within the groups. For the body weight gains, the average final body weight of rabbits obtained were 1340.7g, 1291.3g, 1005.3g, 949.7g and 1089g. For the feed conversion ratio (FCR) of the rabbits was also did not differ significantly (P>0.05). For the feed intake of the rabbits throughout this experiment, feed intake of treatment group MGg which was fed with mash mixture feed and Guinea grass supplementation showed significantly different at (P<0.05) between other treatment groups in Week 3. Feed intakes in other weeks showed not significantly different.